Development of Motion Graphic Video on Class XI Colloid Materials in Increasing Students' Interest in Learning - abd.latif (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2024)
Colloidal material is an abstract material that causes students to have difficulty learning it. The difficulty of colloidal material causes students' interest in learning to decrease. This research aims to produce motion graphic video-based learning media on colloid system material to increase students' interest in learning. This research uses research and development (R&D) methods with a 4-D model, which consists of four stages, namely define, design, develop, and disseminate. However, this development is limited to the development stage only. The product was reviewed by the supervisor and four peer reviewers and then validated by one material expert and one chemist. The quality of the media was assessed by four reviewers (high school/MA chemistry teachers) and responded to by 10 high school/MA students. The Linkert scale is used as a product quality assessment questionnaire sheet and the Guttman scale is used as a student response questionnaire sheet. The product produced in this research is a chemistry learning video on colloid system material. The assessment results from material experts obtained an ideal percentage of 80% and were included in the good category. The results of the media expert assessment obtained an ideal percentage of 85% and were included in the very good category. The assessment results from the reviewers (four SMA/MA chemistry teachers) obtained an ideal percentage of 91.36% and were included in the very good category. The results of the responses of ten high school students obtained an ideal percentage of 95%. Based on the assessment results, it can be concluded that the motion graphic video developed can be used as an alternative learning media for colloid system material to increase interest in learning